The Influence of Celebrity Endorsers, Viral Marketing, and Brand Image on Purchase Decision of Facetology Sunscreen Products in the Shopee Marketplace (A Study on Students of the Universitas Pembangunan Nasional Veteran Jawa Timur) - Dini Dwi Saputri; Jojok Dwiridotjahjono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The development of information technology and the internet has changed traditional business processes to become more dynamic through digital platforms. E-commerce, as one of the innovations in online marketing, makes it easy for consumers to shop practically. Shopee is one of the most popular marketplaces in Indonesia with interactive features that support increased sales. Facetology sunscreen products, with modern marketing strategies such as Celebrity Endorser, Viral Marketing, and strong Brand Image, have succeeded in attracting consumers' attention. Indonesia's location on the equator with high sunlight intensity makes sunscreen a primary need for the community. This study uses an associative type with a quantitative approach, with data collection through distributing questionnaires to 155 active student respondents of UPN "Veteran" East Java who have purchased Facetology sunscreen products on the Shopee marketplace. Data analysis in this study includes testing validity, reliability, classical assumptions, multiple linear regression, and hypothesis testing, all of these analysis processes are carried out using the SPSS program. The results of the study show that the variables Celebrity Endorser, Viral Marketing, and Brand Image have a significant influence, both simultaneously and partially, on purchase decisions.